School, Classroom, and Student Level Indicators of Rural School Effectiveness - Sam Stringfield; Charles Teddlie (Journal of Research in Rural Education, 1991)
This paper compares school, classroom, andstudent level data from matched, high and low outlier schools in rural contexts. Rural data is contrasted with information gathered in urban/suburban schools involved in the same longitudinal study. Following quantitative comparisons from the 1984-85 and 1989-90 school years, three rural case studies are presented. The first is ofa school which appears to have remained a stable positive outlier overthe pastfive years. The secondis ofa stable negative outlier, andthe thirdpresents an improving ruralschool. These data indicate that the instructional processes necessary to obtain student achievement are context-free, but that the organizational and interpersonal processes required to obtain and sustain effective schools vary by context. Evidence of a minimal level below which rural communities do not appear to allow even their least productive schools to fall is interpretedas counter-indicative to a "rural deficit mode/"in elementaryeducation. The paper concludes with a rural school effects research agenda.